Penerapan Asas Keberlangsungan Usaha Dalam Penundaan Kewajiban Pembayaran Utang Untuk Mencegah Pailit (Studi Putusan No. 446/PDT.SUS-PKPU/2021/PN Niaga JKT PST) - Maulana, Muhammad Irfan (Media Hukum Indonesia (MHI), 2025)
This research analyzes the application of the principle of going concern in the PKPU mechanism based on Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations through the normative juridical method, with a statutory approach and a case study of Decision No. 446/Pdt.Sus-PKPU/2021/PN Niaga Central Jakarta. The PKPU application by three creditors against PT Daya Guna Lancar was rejected even though the formal requirements were met, on the grounds that the value of the bill was below Rp500 million in accordance with Perma No. 4 of 2019 concerning Simple Lawsuits. This is considered inappropriate because it has ignored the preventive nature of PKPU as an effort to restructure debt and is contrary to the principle of lex specialis which is emphasized in the dissenting opinion of at least one judge. The results of the study underline the importance of the going concern principle to maintain the sustainability of the debtor's business and the need in avoiding the uniform application of general regulations in PKPU cases.